2015
DOI: 10.1093/jac/dkv114
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and spread of O16-ST131 and O25b-ST131 clones among faecal CTX-M-producing Escherichia coli in healthy individuals in Hunan Province, China

Abstract: ObjectivesThe objectives of this study were to determine CTX-M-producing Escherichia coli ST131 strain prevalence in stool specimens from healthy subjects in central China and to molecularly characterize clonal groups.MethodsFrom November 2013 to January 2014, stool specimens from healthy individuals in Hunan Province were screened for ESBL-producing E. coli using chromogenic medium and CTX-M genotypes and phylogenetic groups were determined. ST131 clonal groups were detected by PCR and characterized for antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 19 publications
3
45
1
Order By: Relevance
“…ST131 with bla CTXM-15 is rare among animal and environmental E. coli isolates ( 26 ). Our analysis of IEH71520, an E. coli isolate from vacuum cleaner dust in the United States ( 15 ), showed that this ST131 isolate belong to the C1-M27 clade. The C1-M27 clade is likely to be present among animal and environmental ST131, and such isolates might act as a hidden reservoir for the introduction of ST131 containing bla CTX-M-27 into human medicine.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…ST131 with bla CTXM-15 is rare among animal and environmental E. coli isolates ( 26 ). Our analysis of IEH71520, an E. coli isolate from vacuum cleaner dust in the United States ( 15 ), showed that this ST131 isolate belong to the C1-M27 clade. The C1-M27 clade is likely to be present among animal and environmental ST131, and such isolates might act as a hidden reservoir for the introduction of ST131 containing bla CTX-M-27 into human medicine.…”
Section: Discussionmentioning
confidence: 94%
“…ST131 containing bla CTX-M-27 responsible for human infections has been reported from various continents ( 2 ) and is especially common among ESBL-producing ExPEC in certain countries, such as Israel, the Czech Republic, and Switzerland ( 2 , 13 , 14 ). CTX-M-27–producing ST131 also is present among nonclinical and nonhuman E. coli isolates, including fecal specimens of healthy children attending day care centers in France; fecal specimens of healthy adults in China, Portugal, and the Netherlands; samples from sick dogs and cats in Japan; samples from water birds from central Europe and Swiss rivers and lakes; and samples of well water from China ( 2 , 10 , 11 , 15 , 23 25 ). The most common ESBL among E. coli ST131 in nonhuman samples is CTX-M-27 ( 2 , 23 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the H30R/C1 clade (fluoroquinolone-resistant) and H30Rx/C2 clade (fluoroquinolone and extended-spectrum cephalosporin-resistant) sub-lineages of this strain have previously expanded globally in association with particular drug resistance mechanisms, including the extended-spectrum beta-lactamase (ESBL) gene, bla CTX-M-15 (clade C2) 21,22 . Given the high rates of community and healthcareassociated infections attributable to ST131 23 , and its capacity to be harbored asymptomatically in the gastrointestinal tract 24 , a stable association of ST131 with bla KPC could have dramatic consequences for the management of E. coli infections 12 .…”
mentioning
confidence: 99%